Bank specific risk and performance: evidence from Nigeria - Oyamendan, Anthony; Adebolanle, Debo-Ajagunna; Asaolu, Adepoju Adeoba; Afolabi, Babatunde (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2026)
Purpose: This study examines the influence of bank-specific risk governance and regulatory compliance on the operational performance of Deposit Money Banks (DMBs) in Nigeria over 2015–2024.Methodology: Secondary panel data for five systemically important DMBs — Access Bank, Zenith Bank, GTCO, First Bank, and UBA — were analysed over a ten-year period. Operational performance is proxied by Return on Assets (ROA). Risk governance predictors include credit risk, liquidity risk, operational risk, regulatory compliance, and bank size as a control variable. Pooled OLS, fixed effects, and random effects panel models were estimated, with the Hausman test selecting the preferred estimator.Results and conclusion: The findings reveal that credit risk exerts a significant negative influence on bank performance, while effective liquidity management and strong regulatory compliance significantly improve performance. Operational risk shows a marginal negative effect. Regulatory compliance emerges as the dominant predictor, affirming that governance quality — beyond mere regulatory adherence — is the primary driver of sustainable profitability among Nigerian DMBs.Implication of findings: Policymakers and bank boards should prioritize embedding genuine compliance culture as a strategic performance lever. The CBN should pair recapitalization directives with standardized governance scorecards to reinforce market discipline.
Keywords: Bank-specific risk; Regulatory compliance; Operational performance; Credit risk; Bank performance